The rediscovery of Astragalus autranii (Fabaceae) on Mt Tomor, south central Albania - Tan, Kit; Shuka, Lulezim; Gjeta, Ermelinda; Vold, Gert (Phytotaxa, 2015)
Astragalus autranii (Fabaceae) placed by Sytin & Podlech in a section of its own (A. sect. Baldaccia) was described from a single specimen in the Barbey-Boissier Herbarium at Geneva. Our observations show that its placement in A. sect. Hololeuce would also be appropriate. The species was first collected by Baldacci in 1892 on Mt Tomor in south central Albania and rediscovered by Markgraf at the locus classicus in June 1928. A complete and amended description of the species is here provided as corolla features were not available in the type material and the flower colour was incorrectly described by Markgraf. Information on habitat, ecology and threat status are also detailed for the first time. Mt Tomor is designated as a protected National Park; however, some of the Astragalus populations may be affected by future road construction.